Membangun Desa Hinas Kanan Kecamatan Hantakan Kabupaten Hulu Sungai Tengah Menjadi Desa Tangguh Bencana (Destana) - Hasanah, Nur; Zulaikha, Siti; Rahmadianty, Pritha; Safira, Adira; Marlina; Utari, Siti Plavia; Puspita, Della; Janah, Miftahul; Perdana, Tiara Selvia; Salam, Ismail Abdi; Rijal, Muhammad Syaiful; Hauzan, Muhammad Rafly Fariz (Hayak Bamara: Jurnal Pengabdian Masyarakat, 2024)
The Meratus Mountains in Hulu Sungai Tengah Regency is an area prone to natural disasters, especially landslides and floods. This is caused by steep topographic characteristics and changes in land cover due to human activities, such as deforestation and land conversion. Hinas Kanan Village, located in Hantakan Sub-district, Hulu Sungai Tengah Regency, is one of the areas vulnerable to floods and landslides. The Disaster Resilient Village (DESTANA) program aims to strengthen community capacity in managing resources and maintaining local wisdom for disaster mitigation. Strengthening the role of the government in terms of resource and technical support, as well as encouraging cooperation between the government, private sector, universities, non-governmental organizations (NGOs), and community organizations to improve community preparedness in the face of disasters. The community service team implemented this program by applying the live-in method, namely living at the program location in Hinas Kanan Village, Hantakan District, Hulu Sungai Tengah Regency, during the period July to September 2024. Activities carried out to support the Desa Tanguh Bencana (DESTANA) program include disaster risk assessments, preparation of Disaster Management Plans (RPB) and Contingency Plans at the village level, socialization on disaster mitigation and hazards, identification of disaster-prone locations, and sketching disaster evacuation strategy maps. With the activities that have been carried out, this can be a step towards developing a resilient and empowered Hinas Kanan Village in terms of mitigating disasters.